2003
DOI: 10.1097/01.ju.0000055471.78783.ae
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and Prognostic Variability of Grade and Lamina Propria Invasion in Stages Ta, T1 Urothelial Carcinoma of the Bladder

Abstract: Observer prognostic variability in staging and grading is considerable with potentially strong implications for patients. Interobserver variation did not decrease using the new 1999 WHO grading classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
77
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(85 citation statements)
references
References 13 publications
3
77
0
5
Order By: Relevance
“…22 Progression was more common in the 20 consensus confirmed stage pT1 cases (25%) than in the 55 pTa and pT1 cases (20%). 22 Tumors that were downstaged to pTa showed less frequent progression than stage pT1 tumors (17 versus 25%), confirmed by review. It was concluded that prognostic variation resulting from observer variability in staging and grading is considerable with significant implications for patient management.…”
Section: Stage Pt0 Carcinomamentioning
confidence: 93%
See 3 more Smart Citations
“…22 Progression was more common in the 20 consensus confirmed stage pT1 cases (25%) than in the 55 pTa and pT1 cases (20%). 22 Tumors that were downstaged to pTa showed less frequent progression than stage pT1 tumors (17 versus 25%), confirmed by review. It was concluded that prognostic variation resulting from observer variability in staging and grading is considerable with significant implications for patient management.…”
Section: Stage Pt0 Carcinomamentioning
confidence: 93%
“…21 In another study, there was complete interobserver agreement on pT1 stage among reviewers in 80% of cases, which rose to 88% after a second review. 22 Of the 63 tumors originally diagnosed as stage pT1, the consensus diagnosis by experienced genitourinary pathologists resulted in downstaging of 35 (56%) to pTa and upstaging of 8 (13%) to pT2-pT3 tumors. 22 Progression was more common in the 20 consensus confirmed stage pT1 cases (25%) than in the 55 pTa and pT1 cases (20%).…”
Section: Stage Pt0 Carcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, to the best of our knowledge, there are only two systematic studies involving more than 100 invasive cancer cases including both univariate and multivariate statistical analyses with respect to recurrence-free and disease-specific survival. 12,24 Moreover, the assessment of tumor grade may show considerable observer variation, 26 and the new two-tiered WHO grading system 27,28 has only rarely been applied with respect to prognostic impact in upper urinary tract UC. 22,24 Thus, other factors accurately predicting the biological potential of this malignancy are required to select candidates for adjuvant therapy.…”
mentioning
confidence: 99%